Hematopoietic stem cell transplantation in a newborn suffering from severe combined immunodeficiency and severe hemophilia A: a case report and review of the literature - Sarah Schober; Michaela Döring; Peter Lang; Johannes Schulte; Martin Olivieri; Vanya Icheva (Research and Practice in Thrombosis and Haemostasis)
Background: Severe combined immunodeficiency (SCID) and severe hemophilia A are 2 rare and potentially life-threatening congenital diseases. The coincidence of these diseases has not been reported so far. Key Clinical Question: We present the first case of a newborn with both diseases. SCID can be treated with hematopoietic stem cell transplantation (HSCT). However, how to successfully manage a newborn with severe hemophilia A during intensive HSCT treatment is the key clinical question of this case report. Clinical Approach: Prophylactic factor (F)VIII substitution during HSCT was performed with an extended half-life FVIII product (efmoroctocog alfa). The platelet count was a major factor influencing the dosage of FVIII. No bleeding complications or FVIII inhibitors occurred during this individualized management. Conclusion: This is the first case report of a newborn suffering from both SCID and severe hemophilia A. HSCT is feasible in this situation without bleeding complications if an individual substitution regimen with FVIII is applied.